Клинический эффект остеогенных препаратов у пациентов с явлениями периимплантита - Марченко, Н.В.; Северинова, С.К.; Бобкова, С.А; Лукаш, А.С.; Кушнир, К.Г. (Таврический медико-биологический вестник, 2009)
Вивчена проблема біологічної несумісності при лікуванні імплантатами. Визначені

критерії оцінки репарації після установки імплантатів. Розроблена комплексна

терапія остеогенними препаратами у осіб зі зниженими процесами репараціі. The problems of biological incompatibility in case of treatment with implants are

researched. The evaluating criterions of reparation process are determined after

implants fixation. Complex therapy with osteogenic preparations are developed for the

patients with weaken process of reparation.